Identification of Peroxiredoxin (PRX) Genes from Pepper Fruits: Involvement in Ripening and Modulation by Nitric Oxide (NO) - Fátima Ramírez-Mellado; Salvador González-Gordo; José M. Palma; Francisco J. Corpas (Antioxidants, 2025)
Peroxiredoxins (Prxs; EC 1.11.1.15) are a group of thiol peroxidases that catalyze the detoxification of H2O2 and other organic hydroperoxides. The ripening of pepper (Capsicum annuum L.) fruit involves significant phenotypic, physiological, and biochemical changes. Based on the available pepper plant genome, eight PRX genes were identified and named CaPRX1, CaPRX1-Cys, CaPRX2B, CaPRX2E, CaPRX2F, CaPRX2-CysBAS1, CaPRX2-CysBAS2, and CaPRX Q. Among these, only CaPRX1-Cys was not detected in the transcriptome (RNA-Seq) of sweet pepper fruits reported previously. This study analyzes the modulation of these seven CaPRX genes during ripening and after treating fruits with nitric oxide (NO) gas. A time-course expression analysis of sweet pepper fruit during ripening revealed that two genes were upregulated (CaPRX1 and CaPRX2E), two were downregulated (CaPRX2B and PRX Q), and three were unaffected (CaPRX2F, CaPRX2-CysBAS1, and CaPRX2-CysBAS2). Gene expression was also studied in three hot pepper varieties with varying capsaicin contents (Piquillo < Padrón < Alegría riojana), showing a differential expression pattern during ripening. Furthermore, NO treatment of sweet pepper fruits triggered the upregulation of CaPRX2B and CaPRXQ genes and the downregulation of CaPRX1 and CaPRX2-CysBAS1 genes, while the other three remained unaffected. Among the CaPrx proteins, four (CaPrx2B, CaPrx2-CysBAS1, CaPrx2-CysBAS2, and CaPrx2E) were identified as susceptible to S-nitrosation, as determined by immunoprecipitation assays with an antibody against S-nitrocysteine and further mass spectrometry analyses. These findings indicate the diversification of PRX genes in pepper fruits and how some of them are regulated by NO, either at the level of gene expression or through protein S-nitrosation, a NO-promoting post-translational modification (PTM). Given that Prxs play a crucial role in stress tolerance, these data suggest that Prxs are vital components of the antioxidant system during pepper fruit ripening, an event that is accompanied by physiological nitro-oxidative stress.